Insomnia dapat Meningkatkan Resiko Depresi pada Lansia - Mochamad Fadly Aditya Ari Saputra; Irma Herliana (Open Access Jakarta Journal of Health Sciences, 2021)
Introduction: Depression is an emotional condition that is usually characterized by extreme sadness, feelings of meaninglessness and guilt, withdrawal from others, sleeplessness, loss of appetite, loss of interest and pleasure in activities that are often carried out. Insomnia is a condition in which a person has difficulty sleeping. Objective: to determine the relationship between insomnia and depression in the elderly. Method: observational with cross-sectional approach. The study population was 32 people, the sample was taken by purposive sampling method of 32 elderly people who fit the criteria. The instruments used were the KSPBJ-IRS and the Geriatric Depression Scale Result: more than half of the elderly who experienced insomnia were 59.4% and more than half of the elderly who experienced depression were 17 people, 54.1%. The results of the study were based on the Chi- Square statistical test with a significance level of 95% (α = 0.05), the p value = 0.00, which is smaller than α (0.05). Conclution: There is a significant relationship between insomnia and depression in the elderly.